MODULATORY EFFECT OF PTEROSTILBENE ON CHANGES IN THE FATTY ACID COMPOSITION IN STREPTOZOTOCIN - NICOTINAMIDE INDUCED DIABETES. - Pidaran Murugan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
P.marsupium has been used in the treatment of toothache, diarrhoea, heartburn, urinary tract infections, boils, sores and skin diseases. Pterocarpus marsupium has been used for many years in the treatment of diabetes mellitus. Pterostilbene was found to be one of the active constituents in the extracts of the heartwood of Pterocarpus marsupium. Pterostilbene is a useful bioactive compound in preventing type 1 diabetes, insulin resistance and type 2 diabetes in animal models. Plants play a major role in the introduction of new therapeutic agents and have received much attention as sources of biologically active substances. The aim of this study was to evaluate the effect of Pterostilbene on blood glucose, plasma insulin and fatty acid composition of total lipids in liver, kidney and brain of control and streptozotocin (STZ)-nicotinamide diabetic rats. The analysis of fatty acids showed that there was a significant increase in the concentrations of palmitic acid (16:1), stearic acid (18:0) and oleic acid (18:1) acid in liver, kidney and brain, whereas the concentrations of linolenic acid (18:3) and arachidonic acid (20:4) were significantly decreased. Oral administration of the Pterostilbene (40 mg/kg body weight) for 45 days to diabetic rats decreased the concentrations of fatty acids, viz., palmitic, stearic, and oleic acid whereas linolenic and arachidonic acid were elevated.